Identification of the Transcriptional Networks and the Involvement in Angiotensin II-Induced Injury after CRISPR/Cas9-Mediated Knockdown of Cyr61 in HEK293T Cells - Junjie Wang; Dongdong Fu; Soulixay Senouthai; Yan Jiang; Rentong Hu; Yanwu You (Mediators of Inflammation)
Background. The transcriptional networks of Cyr61 and its function in cell injury are poorly understood. The present study depicted the lncRNA and mRNA profiles and the involvement in angiotensin II-induced injury after Cyr61 knockdown mediated by CRISPR/Cas9 in HEK293T cells. Methods. HEK293T cells were cultured, and Cyr61 knockdown was achieved by transfection of the CRISPR/Cas9 KO plasmid. lncRNA and mRNA microarrays were used to identify differentially expressed genes (DEGs). Gene ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to determine biofunctions and signaling pathways. RT-PCR was used to validate the microarray results. Cells were divided into four groups: control, Cyr61 knockdown, angiotensin II (Ang II) without Cyr61 knockdown, and Ang II with Cyr61 knockdown. CCK8, western blotting, and flow cytometry analysis were carried out to dissect cellular function. Results. A total of 23184 lncRNAs and 28264 mRNAs were normalized. 26 lncRNAs and 212 mRNAs were upregulated, and 74 lncRNAs and 233 mRNAs were downregulated after Cyr61 knockdown. Analysis of cellular components, molecular functions, biological processes, and regulatory pathways associated with the differentially expressed mRNAs revealed downstream mechanisms of the Cyr61 gene. The differentially expressed genes were affected for small cell lung cancer, axon guidance, Fc gamma R-mediated phagocytosis, MAPK signaling pathway, focal adhesion, insulin resistance, and metabolic pathways. In addition, Cyr61 expression was increased in accordance with induction of cell cycle arrest and apoptosis and inhibition of cell proliferation induced by Ang II. Knockdown of Cyr61 in HEK293T cells promoted cell cycle procession, decreased apoptosis, and promoted cell proliferation. Conclusions. The Cyr61 gene is involved in Ang II-induced injury in HEK293T cells. Functional mechanisms of the differentially expressed lncRNAs and mRNAs as well as identification of metabolic pathways will provide new therapeutic targets for Cyr61-realated diseases.